STRATEGI PENGELOLAAN HUTAN RAKYAT DI KABUPATEN SINJAI - Lenny Marlina Zainal; Amir Tjoneng; Sudirman Numba (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2019)
The Strategy of Social Forest Management in Sinjai Regency was examined using SWOT and AHP methods. This method is carried out by collecting information on internal factors (strengths and weaknesses) and external (opportunities and threats) of respondents consisting of Forest Comunity, Head of Forestry Division of Environment and Forestry OfficeSinjai Regency, the village head involved in the community forest program, & the Forestry Counselor of Sinjai Regency. Based on this information in the development of Social Forestry a strategy should be determined as an alternative strategy that must be applied. To determine the best alternative that will be applied in accordance with the purpose then used the incorporation of SWOT and AHP methods to compare the existing alternatives. The  Social Forest Management Strategy  of Sinjai Regency based on its priorities consists of: (1) Strengthening the role of the group by providing accurate market information (2) Conducting forestry and guidance from the government for the management of the area and the formulation of the management plan. (3) The Government facilitates the licensing to establish a timber industry to increase the value of timber and (4) using agroforestry System.